Foreign Direct Investment and Economic Growth In Indonesia: A Causality Analysis - Fazaalloh, Al Muizzuddin (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.1, Februari 2019 (pp. 1-107)DO - 10.24843/JEKT.2019.v12.i01.p05, 2019)
This study analyse the causality relationship between foreign direct investment (FDI) and economic growth in Indonesia over the period 1970-2015. The method used in this research is Granger causality approach. Results from the estimation show that there is no causal relationship between FDI and economic growth in short and long run. However, the results in this paper indicate that there is a unidirectional causal relationship running from economic growth to FDI in short and long run. It means that economic growth influences FDI inflows in Indonesia.